2010
DOI: 10.1007/s11431-010-4217-8
|View full text |Cite
|
Sign up to set email alerts
|

Field observation of total dissolved gas supersaturation of high-dams

Abstract: One of the possible negative environmental effects of hydropower stations is the supersaturation of total dissolved gas (TDG) downstream of high-dams, which can lead to gas bubble disease or even death of fish. By taking the TDG as the main study object, the paper launched the TDG field observations on Zipingpu, Three Gorges, Ertan, Manwan, Dachaoshan, Gongzui and Ertan dams in China. The factors affecting TDG generation and dissipation were explored. Energy dissipation structures, spill rates and operation pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 4 publications
2
55
0
Order By: Relevance
“…Intermittent exposure may increase the TDG supersaturation level that fish are capable of tolerating or prolong the survival time of fish in supersaturated water, because this scenario provides fish with an opportunity to recover from GBD (Weitkamp and Katz 1980). Weitkamp (1976) intermittently exposed juvenile Chinook Salmon Oncorhynchus tshawytscha to TDG-supersaturated water in the forebay of the Rock Island Dam, Columbia River, by alternatively confining fish in live cages at depths of 0-1 m and 3-4 m, and their results showed that both mortality and the percentage of survivors with signs of GBD were significantly less than in those fish held at constant depths of 0-1 m. According to TDG observations and predictions for high-dam engineering in China, the TDG saturation downstream from the dams in the Gongzui, Tongjiezi, and Xiangjiaba rivers was approximately 130% (Qu et al 2011). Therefore, Prenant's Schizothoracin were most likely exposed intermittently to water at 130% TDG supersaturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermittent exposure may increase the TDG supersaturation level that fish are capable of tolerating or prolong the survival time of fish in supersaturated water, because this scenario provides fish with an opportunity to recover from GBD (Weitkamp and Katz 1980). Weitkamp (1976) intermittently exposed juvenile Chinook Salmon Oncorhynchus tshawytscha to TDG-supersaturated water in the forebay of the Rock Island Dam, Columbia River, by alternatively confining fish in live cages at depths of 0-1 m and 3-4 m, and their results showed that both mortality and the percentage of survivors with signs of GBD were significantly less than in those fish held at constant depths of 0-1 m. According to TDG observations and predictions for high-dam engineering in China, the TDG saturation downstream from the dams in the Gongzui, Tongjiezi, and Xiangjiaba rivers was approximately 130% (Qu et al 2011). Therefore, Prenant's Schizothoracin were most likely exposed intermittently to water at 130% TDG supersaturation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of high dams and super-high dams (100-300 m) have been built in the upper Yangtze River basin in China to meet the country's energy requirements (Zhou et al 2006;Huang and Zheng 2009). When water is allowed to spill over a hydroelectric dam, the intense aeration and pressure in the deep plunge-pool produced by the highvolume discharge leads to supersaturation of total dissolved gases (TDGs) in water downstream from the dams (Hibbs and Gulliver 1997;Qu et al 2011). Total dissolved gas supersaturation can cause fish to develop gas bubble disease (GBD), which can threaten their survival (Weitkamp and Katz 1980).…”
mentioning
confidence: 99%
“…Nevertheless, the impact of dissolved gas super-saturation on larval abundance cannot be exactly estimated in this study, because dissolved gas levels during each flow increase in 2003-2009 were not monitored. However, the appearance of the average discharge of flow increase (Qavg) in the best post-dam function (eqn 5) might partially reflect the negative impact of dissolved gas super-saturation, because levels of dissolved gas super-saturation caused by spills of Three Gorges Dam and Gezhouba Dam were positively linked with the discharge from TGR and Gezhouba Reservoir Qu et al, 2011).…”
Section: Reasons For the Variation In Significant Environmental Factorsmentioning
confidence: 99%
“…Many previous studies have focused on how the TDG dissipation process from supersaturation to saturation is associated with conditions such as water depth, turbulence characteristics, Reynolds number and sediment concentration (Jiang et al, 2008a;Qu, 2011;Feng, 2013;Li et al, 2013). However, there are few studies on the quantitative effects of the water temperature on the supersaturated TDG dissipation process.…”
Section: Introductionmentioning
confidence: 99%